1971
DOI: 10.1128/iai.4.4.331-336.1971
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hemopoietic Colony-Forming Cell Responses in the Pathogenesis of Ectromelia

Abstract: Intraperitoneal injection of complete Freund's adjuvant which caused an extensive cellular response in the reticuloendothelial system greatly increased the severity of infection which resulted from footpad inoculation of ectromelia virus in mice. The mortality was greatest during the proliferative phase of the cellular response, indicated by the colony-forming cell response. Exposure of colony-forming cells to virus in vitro showed that those from normal bone marrow were much less susceptible to virus than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It was also shown that injection of poly(I). poly(C) into mice enhanced the serum activity of a colonystimulating factor, which stimulated growth and differentiation of mouse haemopoietic cells (McNeill & Killen, 1971), and that the polynucleotide stimulated release of a colony-stimulating factor from human monocytes (Ruscetti & Chervenick, 1974). Characterization of the differentiation-stimulating factor in the conditioned medium of macrophages and studies on the relation between this factor and the colony-stimulating factor remain to be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that injection of poly(I). poly(C) into mice enhanced the serum activity of a colonystimulating factor, which stimulated growth and differentiation of mouse haemopoietic cells (McNeill & Killen, 1971), and that the polynucleotide stimulated release of a colony-stimulating factor from human monocytes (Ruscetti & Chervenick, 1974). Characterization of the differentiation-stimulating factor in the conditioned medium of macrophages and studies on the relation between this factor and the colony-stimulating factor remain to be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the response and fate of CFC during ectromelia infection indicated that increased numbers could exist in the presence of a high level of infection within the marrow (9,10). Bro-Jorgensen and Volkert (2), using the in vivo spleen colony assay for pluripotential stem cells, found that mice acutely infected with lymphocytic choriomeningitis virus were incapable of supporting the growth of these cells.…”
mentioning
confidence: 99%